Syncope as an atypical initial presentation of Glanzmann’s thrombasthenia in an adolescent female: a case complicated by anti-Jka–mediated delayed haemolytic transfusion reaction - Madane, Tanvi S.; Chavan, Rohini P. (International Journal of Contemporary Pediatrics, 2026)
Adolescents with Glanzmanns thrombasthenia (GT), a rare inherited disorder of platelet function characterized by defective platelet aggregation despite normal platelet counts, typically present with mucocutaneous bleeding; however, atypical manifestations may cause a delay in diagnosis. Case report describe a 15-year-old girl who had a syncopal episode due to severe iron-deficiency anaemia brought on by persistent menorrhagia. The initial coagulation levels were normal, prompting additional testing, and platelet aggregation tests confirmed GT. She needed coordinated hematology–gynecology care, anaemia correction, and menstrual bleeding stabilization; however, repeated transfusions caused a delayed hemolytic transfusion reaction because of the development of anti-Jka alloantibodies. Iron supplementation, antifibrinolytics, and customized menstrual control were used to treat the patient; alloimmunization required prolonged antigen matching for subsequent transfusions. She showed a good clinical recovery with no recurrence of syncope, highlighting the significance of early diagnosis, prevention of transfusion-related complications, and a multidisciplinary strategy for the best results, as well as the necessity of considering GT in adolescents with unexplained anaemia and normal coagulation profiles, especially in populations with high consanguinity.